The sound environment at preschools and how it may affect children’s hearing - Jansson, Maja (My University, 2017)
Children are being exposed to high sound pressure levels during their stay at the preschool. This might have an effect on the children’s physical and psychological health. Several studies have been made regarding preschool’s sound environment’s effect on the personnel but few have been done including the children. There also is very little research about early sound exposure’s impact on the hearing later in life. This thesis investigates the equivalent A-weighted sound pressure level LA,eq exposure for preschool children during playtime indoors as well as the LA,eq in - and room acoustic properties of - a playroom in preschool. The implementation of the study has been a collaboration between me - a master student in technical acoustics - and a one-year master student in audiology. Six sections within four preschools in the Gothenburg region have been investigated regarding children sound exposure, the sound environment in the playroom and possible effects on their auditory function. To assess the effect of the sound exposure on auditory function, the response of the outer hair cells in the inner ear is measured with DPOAE - Distortion Product Otoacoustic Emissions. DPOAE amplitudes may be reduced after exposure to high sound levels. DPOAE has been measured for seven frequencies between 1 kHz and 10 kHz for children between four and six years old, in the morning and afternoon one day early and one day late in the week. During days of measurements five of the children in the section under investigation wore dosimeters in order to measure their exposure level. There was a fixed microphone hanging from the ceiling in the playroom measuring the sound pressure level during the day and, most of the days, one in the personnel wore a dosimeter as well. Furthermore the acoustic properties of the playrooms has been investigated. The results show that the children are being exposed to high LA,eq levels and that the levels vary substantial among individuals. The average LA,eq during playtime indoors for children in each section ranges from 75.7 dB to 84.0 dB and for the ceiling microphone from 66.9 dB to 76.8 dB with five sections below 70 dB. The reverberation times of the playrooms lie around 0.3 s-0.4 s with exception of one preschool that has somewhat longer reverberation time, especially for lower frequencies. No correlation between reverberation time and sound pressure level in the playrooms could be seen. Preliminary results of the DPOAE measurements show that there might be a reduction of the DPOAE amplitude for the right ear at 3000 Hz.
Keywords: Building Futures; Akustik; Building Futures; Acoustics